Not Limited or Defined but Constructed and Internalized: Exploring Objectivation, Institutionalization, and Legitimation in Donald Barthelme’s “The Balloon” and “I Bought a Little City” - RAMIN, Zohreh; DADAFARID, Reza (Anafora, 2024)
Donald Barthelme’s short fiction is marked by a dashing concentration on everyday life, construction of meaning, and plurality of reality in addition to his playful, metafictional, and fragmentary style. Although a fertile ground for exploring sociopolitical matters, particularly in the mid and late 20th century America, the review of studies on Barthelme’s works highlights a lacuna in the application of conceivably pertinent sociological and political theories on Barthelme’s short stories. Accordingly, Peter L. Berger and Thomas Luckmann’s The Social Construction of Reality (1966) could be a congruous theory with Barthelme’s sociological concerns in his short fiction. In their treatise, Berger and Luckmann see reality as a kind of “collective fiction” that is constructed by the processes of institutionalization, socialization, and everyday social interaction, particularly through language. In this article, we read “The Balloon” and “I Bought a Little City,” which are selected thematically, in light of “society as objective reality” through the concepts of objectivation, institutionalization, and legitimation. Linking literature and sociology, we aim to pinpoint how the stories observe, unveil, and potentially critique construction of meaning and the real workings of the processes in the social construction of reality.